2014
DOI: 10.1105/tpc.114.127373
|View full text |Cite
|
Sign up to set email alerts
|

The Light-Harvesting Chlorophyll a/b Binding Proteins Lhcb1 and Lhcb2 Play Complementary Roles during State Transitions in Arabidopsis

Abstract: ORCID ID: 0000-0002-7906-6891 (S.J.)Photosynthetic light harvesting in plants is regulated by phosphorylation-driven state transitions: functional redistributions of the major trimeric light-harvesting complex II (LHCII) to balance the relative excitation of photosystem I and photosystem II. State transitions are driven by reversible LHCII phosphorylation by the STN7 kinase and PPH1/TAP38 phosphatase. LHCII trimers are composed of Lhcb1, Lhcb2, and Lhcb3 proteins in various trimeric configurations. Here, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
200
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 254 publications
(231 citation statements)
references
References 69 publications
(95 reference statements)
22
200
0
Order By: Relevance
“…This was previously shown in an analysis of antisense lines deficient in Lhcb1 or Lhcb2 (Pietrzykowska et al, 2014). The lack of cross reactivity was further confirmed using recombinant proteins expressed in Escherichia coli (Supplemental Fig.…”
Section: An Improved Phos-tag Page Protocol Allows a Quantitative Meamentioning
confidence: 74%
See 4 more Smart Citations
“…This was previously shown in an analysis of antisense lines deficient in Lhcb1 or Lhcb2 (Pietrzykowska et al, 2014). The lack of cross reactivity was further confirmed using recombinant proteins expressed in Escherichia coli (Supplemental Fig.…”
Section: An Improved Phos-tag Page Protocol Allows a Quantitative Meamentioning
confidence: 74%
“…Lhcb1 could largely replace Lhcb2 in the lines lacking Lhcb2. However these Lhcb2 knock-down mutants could not assemble the PSI-LHCII supercomplex or undergo state transitions (Pietrzykowska et al, 2014). Using phosphospecific antisera, it was also observed that PSI-LHCII is enriched in P-Lhcb2 but lacks P-Lhcb1 (Leoni et al, 2013).…”
Section: Antenna Phosphorylation In the Psi-lhcii State Transition Sumentioning
confidence: 83%
See 3 more Smart Citations